ANALISIS FILOGENETIK Curcuma zedoaria (TEMU PUTIH) BERDASARKAN GEN INTERNAL TRANSCRIBED SPACER (ITS) - Yuliandini Pangestika; Anto Budiharjo; Hermin Pancasakti Kusumaningrum (Jurnal Akademika Biologi, 2015)
Curcuma zedoaria belongs to Zingiberaceae family which has a local name white turmeric. This local name is not only used by C. zedoaria, but also used by C. mangga and Kaempferia rotunda. This problem leads to incorrect selection of ingredients, so that the therapeutic effect can not to achieved. Therefore phylogenetic analysis is important to differentiate three types of these plants. Phylogenetic analysis illustrated the taxonomic classification of organisms based on evolutionary history. Sequence which used in this study was Internal Transcribed Spacer (ITS). ITS flanked by the coding region of 18S, 5.8S and 26S rDNA on each unit in a series of chromosomes. Aimed of this study was to perform phylogenetic analysis of C. zedoaria which from Indonesia based on ITS gene sequences. Methods included were DNA isolation using Doyle and Doyle method (1987), ITS gene amplification using ITS1 and ITS4 primer, analysis of ITS gene sequences using Basic Local Aligment Search Tool (BLAST), and construction of phylogenetic trees using MEGA6 by neighbor-joining tree method and bootstrap method with 1000 replications. DNA isolation resulted DNA concentration of 853 ng/µl and purity value of 2.17. Amplification of  ITS region resulted in 700 bp product. Result of homology search showed C. zedoaria had homology with C. zedoaria voucher JLS 71432 clone 4 from Czezh Republic with 72 % homology and 3 % gap. Phylogenetic analysis showed that white turmeric collected in this study was C. zedoaria and different from C. mangga and K. rotunda. This study concluded that C. zedoaria different from C. zedoaria from the Czech Republic, however both were in a Curcuma monophyletic group.Keywords: Curcuma zedoaria, Internal Transcribed  Spacer,  phylogenetic, white turmeric